Women want male partner engagement in antenatal care services: A qualitative study of pregnant women from rural South Africa. - Carolyn M Audet; Daniel E Sack; Godfrey H Ndlovu; Caroline Morkel; Jacob Harris; Ryan G Wagner; Tshegofatso M Seabi (PLoS ONE)
Introduction Evidence strongly shows that a supportive, involved male partner facilitates maternal HIV testing during pregnancy, increases maternal antiretroviral (ART) adherence and increases HIV-free infant survival. Partner engagement in antenatal care (ANC) is influential; however, the most effective strategy to engage male partners is currently unknown. Engaging pregnant women to understand whether male partner involvement is welcome in ANC, what this involvement entails and how best to invite their partner is an important first step in determining how best to engage male partners. Methods We interviewed 36 pregnant women receiving ANC services at a district hospital in rural Mpumalanga, South Africa to assess the strengths and weaknesses of their current relationship, the type of partner support they receive, whether they would like their male partner to be involved in their ANC, and how best to invite their male partner to their appointments. We conducted a thematic analysis of the qualitative interviews using MAXQDA software. Results Financial, emotional, and physical support were noted as important aspects of support currently provided by male partners, with most pregnant women wanting their partners to engage in ANC services during pregnancy. Preferred engagement strategies included participation in couple-based HIV testing and counseling, regular ANC appointment attendance, and delivery room presence. Women who reported a positive relationship with her partner were more likely to prefer inviting their partner without health facility assistance, while those who reported challenges in their relationship preferred assistance through a letter or community health worker. Pregnant women perceived regular business hours (due to their partner being employed and unable to take off work) and having a partner involved in multiple relationships as barriers in getting their partner to attend ANC services. Discussion Rural South African women, even those in unsatisfactory relationships want their male partners to attend their ANC visits and birth. To make this possible, health facilities will have to tailor male partner engagement outreach strategies to the preferences and needs of the pregnant woman.